Produção de lipase fúngica a partir de subprodutos do processamento de soja - Tombini, Jessica (2015)
Microbial lipases gain great commercial prominence because they have high specificity and stability in their reactions, allowing the lipase industry to be composed of several segments, such as food, pharmaceutical, textile, wastewater treatment and reuse of agricultural waste. Seeking for the production of lipolytic enzymes from these substrates, four wild strains of filamentous fungi was assessed by solid state fermentations. The soybean meal biomass showed higher potential as substrate for lipase production without nutritional supplementation of medium. The fungal isolated S4 (Penicillium sp) had the highest lipolytic potential among the evaluated fungi. A rotational central composite design 23 demonstrated that culture parameters spore concentration and moisture are variables that affect enzyme production by the fungus. The cultivation time demonstrated no significant effect on lipase production and increased production of lipase (73,85 UL-1) was obtained when using inoculum at a concentration of 105 spores / mL and culture medium with 54% moisture. Crude lipase showed optimum conditions of activity at 35 ° C at pH 8.0 and it was active in the pH range between 6 and 11. Enzymatic extract showed relative activity of 50% among the temperature of 20 ° C and 40 ° C (30 minutes of heating) and kept 50% of its activity when heated at 40 ° C for 60 minutes. The ions Ca2+, K+, Cu2+ (2 mM) and I- showed activating effect on the lipolytic activity of the enzyme, unlike ion Fe2+, which showed strong inhibition. The crude enzyme was sensitive to the presence of organic solvents as acetone, DMSO, methanol, propanol and the enzyme was activated by the hexane solvent.